Serum LH/FSH ratios in 87 infants with differences of sex development - Marie Lindhardt Ljubicic; Trine Holm Johannsen; Margit Bistrup Fischer; Emmie N Upners; Alexander S Busch; Katharina M Main; Anna-Maria Andersson; Casper P Hagen; Anders Juul (Endocrine Connections, 2023)
The ratio between luteinizing hormone (LH) and follicle-stimulating hormone (FSH) has previously been described as an excellent marker of sex in healthy infants. However, LH/ FSH remains not fully described in patients with differences of sex development (DSD). The aim was therefore to describe LH/FSH in infants with DSD. This was a retrospective study of DSD patients, all aged 0–1.2 years. In total, 87 infants with DSD and at least one serum sample per infant were included. Longitudinal samples from single patients were included whenever possible. Serum LH/FSH ratios in these patients were plotted against recently published age-related and sex-dimorphic cutoffs. Overall, LH/FSH sometimes corresponded to assigned sex without any obvious pattern in terms of diagnoses. LH/FSH corresponded to the biological sex in all patients with Turner or Klinefelter syndrome. In patients with 46,XX or 46,XY DSD (except congenital adrenal hyperplasia (CAH)), the ratios did not correspond to the assigned sex in all cases and were interchangeably within the male and female range. In patients with CAH, the ratio corresponded to biological sex (based on sex chromosomes) in some cases but also ranged across the cutoffs. In the 15 patients with 45,X/46,XY mosaicism, the LH/FSH ratios corresponded to the assigned sex in all cases (12 were raised as males, 3 as females) and at all time points in cases with multiple sampling. While this study describes LH/FSH in infants with DSD, the exact clinical role of the ratio in the management of these patients remains to be further elucidated.